Centring Home in Mobility: Overseas Chinese Christians and the Construction of a Node of Religious Belonging in China. - Lau, Sin Wen (Asian Studies Review, 2017)
Although the formation of overseas Chinese communities in cities constitutes a major trend in reform era China, conceptualisations of the relationship between the overseas Chinese and China remain divided. The overseas Chinese are seen either as temporary migrants with little attachment to the country or as inescapably connected to China through native place. This paper aims to move beyond this dichotomous understanding by examining the processes of place-making among overseas Chinese Christians in Shanghai, one of China’s major urban centres. It draws on ethnographic research conducted within a Christian network and illustrates how these Christians negotiated the forces of global capitalism, state regulations, and an indigenous Christian trajectory to construct a religious territory and centre Shanghai as home. By showing how they understand their place as Christians, this paper argues that economic restructuring in the reform period enabled the emergence of cities as new centres where the overseas Chinese are making a place for themselves. It contributes to the literature on the overseas Chinese and China by redirecting attention from the native place as the locus of overseas Chinese attachment to the city as a new centre of belonging.